From Cycles to Series—Shakespeare’s History Plays Adapted to the Small Screen - Földváry, Kinga (FOCUS: Papers in English Literary and Cultural Studies, 2014)
The primary focus of this article is television adaptations of Shakespeare’s history plays, more precisely the eight dramas that make up the two tetralogies (the First or Minor Tetralogy, comprising Henry VI Parts 1, 2, and 3, and Richard III; and the Second or Major Tetralogy, comprising Richard II, Henry IV Parts 1 and 2, and Henry V), are thus associated with the notions of continuity and interconnectedness. I will examine several attempts at filming one or both of the tetralogies, to see how the new medium—in this case, television, rather than the large screen of the cinema—uses or transforms, creates or recreates the elements that can reinforce cohesion among the individual units.